Controlling the Properties of a-ZTO and a-IGZO via Low Temperature Annealing and Novel Layered Structures - Kaisha, Aitkazy (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
This thesis deals with the broader implications of amorphous ZnSnO (a-ZTO) growth via two synthesis methods, examining the in-situ resistivity monitoring approach to optimising a low-annealing temperature <300 ?C and exploring oxide-oxide lamination system is to control the properties of TCOs. Chapter 4 describes the effects of reactive and nonreactive sputtering methods on the growth of a-ZTO. Two techniques broadly correspond to an oxygen-poor and rich atmosphere. Both approaches lead to identical conductivities of a-ZTO films. The best properties are found in two distinct compositions. The elemental ratio shifts were found to be due to shifts in local bond arrangements. These local bond arrangements were confirmed by Raman spectroscopy. This demonstrates the complex relationship between growth conditions and oxygen structure in a-ZTO. I will then discuss in-situ post-deposition annealing to improve the conductivity of a-ZTO films at lower annealing temperature <300 ?C. The optimal conditions for annealing were examined via a specialist system that allowed in-situ monitoring of the resistivity in the annealing process. The system also allows for control of the annealing atmosphere. This setup examined the impacts of different annealing parameters on final film properties. The parameters examined include the gas composition of the annealing atmosphere, the relationship between annealing time and temperatures, and the thickness of the films. A lower annealing point of 220 ?C temperature was identified that produced similar conductivities to those attained at a higher temperature of 300 ?C. The successful post-deposition treatment with a highly conductive film on a Kapton substrate demonstrated the benefits of a well-controlled annealing approach. Chapter 5 explored a layered structure to achieve a low carrier density of TCOs. This method involved inserting an ultra-thin layer of an alternative oxide between two TCO material layers. Two common ultra-thin TCOs and insulators were used to examine the layered structures. SiOx used as one of the layers in the trilayer that showed a marked decrease in carrier density in the insertion of SiOx in the laminated films. The free carrier density of a-ZTO/SiOx/a-ZTO declined by a factor of three compared to a similar thickness a-ZTO, but just 40% of reduction in carrier mobility was found. The insertion of TiOx layers into the laminated oxides was also investigated in a similar tri-layer arrangement. Although the TiOx layer suppressed the density of current carriers less effectively compared to the layer of SiOx, in a-ZTO/TiOx/a-ZTO trilayers, a significantly reduced influence on carrier mobility was observed. The lowest density of free carriers in the trilayer of a-ZTO/Insulator/a-ZTO structures was established by a small thickness 2nm thick SiOx and TiOx insulators. By utilising a broader range of characterisation techniques, the carrier concentration drop in a-IGZO/SiOx/a-IGZO was assessed (a-IGZO is amorphous InGaZnO). a-IGZO was selected for this study as the effect is markedly similar to a-ZTO while significantly enhancing in magnitude. The film growth was established to be continuous regardless of thickness by SEM due to discontinuous leads to increase resistivity. No variation in oxygen structures in trilayer structures was confirmed via in-situ XPS studies. The effect of oxygen flow on the SiOx layer in trilayers was studied, and the oxygen flow eliminated a reduction in charge carrier in trilayers.
APPROVED